(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
The main purpose of this study was to investigate Online Resources and Management of Private Secondary Schools in Calebar Municipality, The survey research design was adopted for the study. A sample of fifty-four (54) principals was used, using the purposive sampling technique, four null hypotheses were formulated. A structured questionnaire was the instrument source of data collection. Pearson product moment correlation analysis and independent t-test analysis were adopted as statistical tools to test the hypotheses at .05 level of significance with a critical t-value of 2.00 and critical r-value of 0.26 with 52 degree of freedom. The result of the findings revealed that the use of online registration, of e-payment, online instructional delivery and the use of internet public library have significant relationship with the management of private secondary schools in Calabar Municipality. Based on the findings, it was therefore recommend that, Parents Teachers Association (PTA) should support the private schools to motivate them in providing quality teaching-learning resources and the Ministry of Education should also make it very mandatory for private secondary schools to activate the online resources to upgrade to the status of the global world.